Ecofriendly Dyeing of UV-Irradiated Cotton Using Extracts of Acacia nilotica Bark (Kikar) as Source of Quercetin - Adeel, Shahid; Hanif, Rashid; Zuber, Muhammad; Muneer, Majid; Rehman, Fazal-ur-; Haq, Ehsan-ul- (Asian Journal of Chemistry, 2014)
Increasing awareness about safe products in textiles has developed the worldwide choice in natural colour based textiles. For the present study, barks of Acacia nilotica (Kikar) has been selected as source of natural flavone dye (querecetin). Both cotton fabrics and dye powder were exposed to UV radiations for 30, 45, 60, 90 and 120 min. Later on the dye was extracted using irradiated (RP) and un-irradiated dye powder (NRP) followed by dyeing of irradiated (RC) and un-irradiated fabric (NRC). Different dyeing variables such as temperature, time, pH, liquor concentration (M:L) and electrolyte concentration were optimized and dyeing was performed at these optimum coniditions. To improve colour strength and colour fastness properties different concentrations of mordants such as Cu (copper sulphate), Al (aluminum sulphate), Fe (iron sulphate) and tannic acid were employed. ISO standard methods were employed to determine the colour fastness to light, washing and rubbing to observe the effect of UV radiation on these fastness properties. The fabrics investigated in CIE Lab system using spectraflash showed that exposure for 90 min modifies the surface of fabric and dyeing for 50 min at 55 ºC, using 8 g/100 mL of salt using dye bath of pH 6 provides the best colour strength. It is also found that iron is the best mordant among other used that improves the colour fastness properties from moderate to good.